Odpowiedzi

Najlepsza Odpowiedź!
2009-11-10T15:50:06+01:00
A) d×(-3)×c= -3cd
b) 3(-x)(-a)= 3ax
c) xy×½y= 1/2 x²y²
d) 2cd-(-9)×d= 18cd²x
e) ¼abb×(-2a)= - 1/2 a²b²
f) a²×4×(-a)×(-5)= 20a³
g) 3x²y×(-jedna szusta xy)=1/3 x (do czwartej) y²
h) -3(-x)(-x)(-y)= 3x²y
i) 0.2tsts²×(-15)= -3 t²s³
2009-11-10T16:00:31+01:00
A) d×(-3)×c= -3cd
b) 3(-x)(-a)= 3ax
c) xy×½y= 1/2 x²y²
d) 2cd-(-9)×d= 18cd²x
e) ¼abb×(-2a)= - 1/2 a²b²
f) a²×4×(-a)×(-5)= 20a³
g) 3x²y×(-jedna szusta xy)=1/3 x (do czwartej) y²
h) -3(-x)(-x)(-y)= 3x²y
i) 0.2tsts²×(-15)= -3 t²s³

To jest dobrze ;]
2009-11-10T16:21:51+01:00
A) d×(-3)×c= -3cd
b) 3(-x)(-a)= 3ax
c) xy×½y= 1/2 x²y²
d) 2cd-(-9)×d= 18cd²x
e) ¼abb×(-2a)= - 1/2 a²b²
f) a²×4×(-a)×(-5)= 20a³
g) 3x²y× -⅙ xy=⅓ x⁴ y²
h) -3(-x)(-x)(-y)= 3x²y
i) 0.2tsts²×(-15)=-15*0.2 t²s³=-3 t²s³
Mam nadzieje ,że pomogłem